Signs of God : Miracles and their Interpretation. - Corner, Mark (Ashgate Pub., 2007)
Signs of God reveals why discussion of the nature of miracles is of central rather than marginal importance where belief in God is concerned. This accessible book examines the nature of miracles both in philosophical and historical terms, and concludes that, whether or not miracles happen, it is difficult to see how religious belief could survive without them.